Mid-Upper Arm Circumference (MUAC) shows strong geographical variations in children with edema: results from 2277 surveys in 55 countries - Jose Luis Alvarez; Nicky Dent; L. Browne; Mark Myatt; André Briend (BMC, 2018)
Abstract Background Severe acute malnutrition (SAM) is defined by a mid-upper arm circumference (MUAC) less than 115 mm or a weight-for-height z-score (WHZ) less than − 3 but also by the presence of bilateral pitting edema, also known as kwashiorkor or edematous malnutrition. Although edematous malnutrition is a life threatening condition, it has not been prioritized in recent research and has been neglected in global health initiatives. Methods Two thousand two hundred and seventy-seven survey datasets were collected, and the age, sex, weight, height, MUAC and the presence or absence of edema were analyzed for more than 1.7 million children of 6-59 months from 55 countries, covering the period of 1992 to 2015. Results During the last 10 years, the prevalence of nutritional edema was estimated at less than 1% in most of the countries where data were available. Some countries in Central and South Africa, as well as Haiti in the Caribbean, reported higher prevalence, and Yemen, Zimbabwe and the Democratic Republic of Congo reported prevalence between 1 and 2%. Surveys from a significant number of countries in Africa indicated that more than a third of SAM cases defined by MUAC < 115 mm had edema, including Malawi, Rwanda, Zambia, Togo and Cameroon. Children with edema were consistently shown across various analyses to have a significantly lower median MUAC than children without edema. However, the MUAC distribution had a large spread, with many children with edema having a MUAC > 115 mm, and this varied widely between countries, with median MUAC in edematous children ranging from 102 mm (Mali) to 162 mm (Sri Lanka). The proportion of SAM children with edema was found to be higher for older children. Conclusions This study provides the most recent geographical distribution of nutritional edema and demonstrates that edema is a common manifestation of SAM, mainly occurring in Central Africa. The associated nutritional status, as assessed by MUAC, shows strong variation among children with edema. A more systematic and standardized system is required to collect data on edema in order to facilitate prevention, screening, referral and treatment of edematous malnutrition.